The Role of Echocardiogram in Outpatient Paediatric Chest Pain - Richo Wijaya; Tina C. L. Tobing (PT Kalbe Farma Tbk., 2019)
Chest pain in children usually makes both patients and family anxious, but - in contrast to among adults - mostly is not caused by serious disease. American College of Cardiology published criteria for initial transthoracic echocardiography in outpatient setting. Nyeri dada pada anak pada umumnya menimbulkan kecemasan baik pada anak maupun keluarga; tetapi biasanya tidak disebabkan oleh penyakit serius, lain halnya dengan pada orang dewasa. American College of Cardiology mengeluarkan Appropriate Use Criteria penggunaan ekokardiografi transtorakal pada pasien rawat jalan kardiologi.